Evaluation of spraying efficiency of a mixture of bacteria, Pseudomonas fluorescenes and Bacillus subtilis and Albion preparation on shoots of tomato plants in resistance to cucumber mosaic virus (Journal of the College of Basic Education, 2022)
The aim of the research was to evaluate the efficiency of each of the bacteria Pseudomonas fluorescens, Bacillus subtilis and Albion preparation as factors inducing resistance of tomato plants against Cucumber mosaic cucumovirus when they were used as a spray on the shoots of the plant under greenhouse conditions. The results showed that there were significant effects of the aforementioned factors in reducing the rate and severity of infection and increasing the growth parameters of the studied tomato plants compared to the control treatment, which was infected with the virus alone. The results showed a high efficiency of the mixture of the two types of bacteria, P. fluorescens and B. subtilis